HUBUNGAN RIWAYAT JATUH TERHADAP FUNGSI EKSTREMITAS BAWAH PADA LANJUT USIA - Susilawati, Indri; Mulyajaya, Muhammad Satria; Suprawesta, Lalu; Putri, Ni Ketut Dewita (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2026)
Falls are a common public health problem in older adults and are associated with declines in physical function, disability, and reduced quality of life. This study aimed to examine the association between a history of falls in the past six months and lower extremity functional performance among community-dwelling older adults. A cross-sectional observational study was conducted in 50 community-dwelling older adults. Fall history was obtained through interviews, while lower extremity function was assessed using the Five Times Sit-to-Stand Test (FTSTS). Data were analyzed using the Mann–Whitney U test and binary logistic regression. The results showed that 10 of 50 participants (20%) had a history of falls, and this group had a significantly longer FTSTS time (19.26 seconds) than those without a history of falls (14.05 seconds), with a significant association between FTSTS time and fall history (p = 0.018). Each 1-second increase in FTSTS time was associated with an approximately 20% higher odds of falling (odds ratio [OR] = 1.20; 95% confidence interval [CI] = 1.02–1.40; p = 0.024). These findings indicate that poorer lower extremity function is an important factor associated with falls among community-dwelling older adults, and that the FTSTS may serve as a simple screening tool to identify older adults at higher risk of falls in primary care and community settings.